SİYASET FELSEFESİ NEDİR? - Neşet Toku (Felsefe Dünyası)
The philosophy of politics is an intellectual activity which has emerged in order to reach the information of a qualified life and society and thus it looks for the answers of the following fundamental questions; "who gets what?" and "says who?". The term "philosophy" in the phrase of "the philosophy of politics" points out the treatment of this subject and the term "politics" states both the subject and its function. The terms "philosophy" and "politics", also, express to be comprehensive in universal meaning and the final aims of the mankind such as freedom and equality, respectively. In contrast to the philosophies that Nietzsche calls them as monologue scholarly, the lost goods, the secret which is needed not to disclose or academic chattering without danger, it is a rational scream which invites the man not to give up the idea for the qualified life and society